Ceftriaxone Resistance – A caution for judicial antibiotic use - Jacson, Janice (Indian Journal of Pharmacy & Drug Studies, 2023)
Ceftriaxone is a broad-spectrum antibiotic that is effective against both Gram-negative and Gram-positive isolates. Ceftriaxone resistance research is useful in determining its current status. As a result, we aimed to understand the prevalence of Ceftriaxone resistance in bacteria isolated from various clinical specimens. Resistance to ceftriaxone has been steadily increasing and demands immediate attention. Ceftriaxone resistance prevention mechanisms must be strictly enforced. The appropriate drugs should be chosen based on susceptibility patterns. In summary, ceftriaxone should be considered in the initial treatment of seriously ill patients with infections of unknown aetiology when Gram-negative aerobes (other than Pseudomonas species) are the suspected pathogens, and in patients with Gram-negative organisms with suspected or demonstrated resistance to other antibiotics. This review summarizes the advent of ceftriaxone resistance among various organisms across the globe.